Borçlar hukukunda cezai şartın indirilmesi - Özmen, Adem (My University, 2011)
Borcun hiç veya gereği gibi ifa edilmemesi halinde ödenmesi gereken ekonomik değere sahip asıl borçtan ayrı edim olan cezai şartın aşırı yüksek olması durumunda BK md 161/ III de yer alan düzenleme devreye girer. BK md 161/ III de kanun koyucu hâkime aşırı olan cezai şartı indirmesi için takdir yetkisi vermiştir. Borçlunun talebi üzerine hâkim kendisine tanınan bu yetkiye dayanarak alacaklının yararları, borçlunun kusuru ve tarafların ekonomik durumlarını Medeni Kanun md 4 de yer alan düzenleme ile birlikte değerlendirerek hakkaniyet gereği aşırı olan cezai şartı uygun bir miktara indirir. Hâkimin bu kararı yargısal yenilik doğuran bir karardır. TTK md 24 deki düzenlemeye göre tacirin ticari işletmesine ilişkin borçlarında cezai şart kararlaştırılmış ise tacir olan kişi bunun aşırı olduğunu ileri sürerek hâkimden indirim talebinde bulunamaz. Fakat kararlaştırılan cezai şartın tacir sıfatına sahip borçlunun ekonomik açıdan yıkımına yol açacak derecede yüksek olması durumunda ahlaka adaba ve emredici hükümlere, kararlaştırılan miktar yönüyle aykırı düşen cezai şartın sırf tacirin basiretli davranması gerektiğinden bahisle müdahale edilmeyeceğini söylemek hukuka ve hakkaniyete aykırı düşecektir. Bu durumda BK md 19-20 de yer alan düzenleme uyarınca borçlunun yıkımına yol açan onu ekonomik yönden çökerten cezai şartın indirime tabi tutulması mümkündür. Cezai Şart, Cezai Şartın Hukuki Niteliği, Borç, İndirim

In case the penalty constituting a sanction separately from the primary obligation that has an payable economic value where the obligation is never or not duly fulfilled is excessively high, the regulation set forth in Article 161/ III of the Code of Obligations applies. In Article 161/ III of the Code of Obligations, the legislator confers upon the judge the judicial discretion to reduce the excessively high penal sanction. Upon the request of the obliger, the judge, based upon such authority conferred upon him/ her, assesses the economic benefits of the creditor, the failure of the obliger and economic conditions of the parties in view of the regulation provided for in Article 4 of the Code of Obligations, and duly reduces the excessively high penal sanction in equity. Such discretion of the judge constitutes a judgement introducing judicial renovation. Pursuant to regulation provided for in Article 24 of the Turkish Commercial Code, if a penal sanction is introduced for obligations of the merchant regarding his/ her business, such merchant may not claim a reduction from the judge by putting forward that such obligation is high. However, where the penal sanction introduced is so high that it may harm the economic condition of the merchant who is the obliger, it would conflict with the law and equity to argue that the penal sanction offending good morals and imperative provisions in terms of amount could not be intervened in merely due to the requirement that the obliger should act prudently. In this case, pursuant to the regulation provided for in Article 19-20 of the Code of Obligations, it is possible that the penal sanction that economically harms the obliger may be reduced. Key Words : Penalty Clause, Legal Nature Of Penalty Clause, Dept, Discount
Keywords: Borçlar Hukuku; Özel Hukuk